Influence of Different Preparation Processes on the Mechanical Properties of Carbon Nanotube-Reinforced Copper Matrix Composites - Guo, C.H.; Zhan, Z.J.; Zhang, D.D. (Проблемы прочности, 2015)
Experiments on the uniform distribution of carbon nanotubes in the copper matrix using different ball milling methods were performed. The effect of different preparation processes for carbon nanotube (CNT)-reinforced copper matrix composites on their conductivity and mechanical properties was also analyzed. High-performance carbon nanotube-reinforced copper matrix composites containing 1 vol.% CNT by the best preparation process termed flake ball milling (FBM) possess good interface bonding strength not only with CNT evenly dispersed in the copper matrix but also with the CNT morphology and structure having the utmost integrity. Tensile strength increased by 30% with an elongation of 26% and electrical conductivity of 85% IACS as compared to a pure copper block prepared from the same FBM powders. Выполнены эксперименты по оценке равномерности распределения углеродных нанотрубок в медной матрице с использованием разных методов размола в шаровой мельнице. Проанализировано влияние различных методов изготовления композиционных материалов с медной матрицей, упрочненных углеродными нанотрубками, на их электропроводность и механические свойства. Высококачественные композиционные материалы (содержат 1 об.% углеродных нанотрубок), изготовляемые наиболее эффективным способом, получившим навание размол в шаровой мельнице для придания пластинчатой структуры , приобретают хорошую прочность сцепления на поверхности контакта не только при равномерном распределении углеродных нанотрубок в медной матрице, но и при максимальной целостности их морфологии и структуры. Предел прочности при растяжении возрастал на 30% при удлинении 26% и электропроводности 85% по стандарту IACS по сравнению с заготовкой из чистой меди, изготовленной из тех же пластинчатых порошков.